Pop-Up Book “Satua Bali I Buta Teken I Rumpuh” on the Topic of the Sense of Sight to Improve Scientific Literacy for Fifth Grade Elementary School Students - I Gede Dimas Rangga Wijaya; I Gede Margunayasa; Luh Putu Sri Lestari (Undiksha Press, 2025)
The low scientific literacy of elementary school students is caused by the lack of contextual learning media that connect science content (IPAS) with local culture, such as folktales. This study aims to develop a Pop-Up Book media titled Satua Bali I Buta Teken I Rumpuh. This is a development research using the ADDIE model. The research subjects were fifth-grade elementary school students. Data were collected through validation questionnaires by material and media experts, response questionnaires from teachers and students, as well as pretest and posttest. The instruments used included validation sheets, rating scale questionnaires, and multiple-choice test questions. The data were analyzed using descriptive quantitative methods. Based on the results of the validity test by media and material experts, the Pop-Up Book media obtained scores of 3.76 and 3.83, respectively, categorized as very good. The practicality test showed highly positive results, with a score of 100% from teachers and 94.06% from students, indicating that the media is very practical for use in learning. The effectiveness test conducted on 31 fifth-grade students revealed a significant difference in improving students’ scientific literacy, with a significance value of 0.00 in the correlated t-test. Thus, it can be concluded that the Satua Bali I Buta Teken I Rumpuh Pop-Up Book media is valid, practical, and effective in enhancing elementary school students’ scientific literacy.